STRATEGI INTERNALISASI NILAI ANTI KORUPSI DALAM MEMBENTUK KARAKTER INTEGRITAS MAHASISWA - Adinda Putri Wahyuni; Tresa Alvianty (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption is a serious issue that can damage the social, economic, and moral order of a nation. Therefore, systematic efforts are needed to instill anti-corruption values from an early stage, particularly in higher education institutions. This study aims to examine strategies for internalizing anti-corruption values in shaping students’ integrity. The method used is a qualitative approach through literature review and descriptive analysis. The results indicate that the internalization of anti-corruption values can be carried out through curriculum integration, lecturers’ role modeling, extracurricular activities, and the habituation of an academic culture that upholds honesty and responsibility. In addition, a supportive campus environment plays an important role in shaping students’ integrity. With appropriate and sustainable strategies, students are expected to develop anti-corruption attitudes and become agents of change in creating a clean and integrity-based society